Dissent on assembly, a subtle rejection within opposition against Anwar - Analysts - New Sabah Times English, (KK) (New Sabah Times English (kk), 2013)
KUALA LUMPUR: The actions of several Pakatan Rakyat leaders in disagreeing with the desire of pro-opposition groups to topple the Barisan Nasional (BN) government through street demonstrations and violence have indirectly rejected PKR de facto leader Datuk Seri Anwar Ibrahim say political analysts.